The Indo-Pakistani Dispute over Jammu and Kashmir : A Frozen Conflict in South Asia - Brutyan, Armenuhi; Garlick, Jeremy; Halimzai, Pamir; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The Kashmir dispute is one of the world's most dangerous conflicts between two possessors of nuclear weapons, India and Pakistan. Kashmir is a region with a majority Muslim population that has not been granted the right of self-determination to decide if they want to remain as part of India or join Pakistan. The conflict has lasted for almost seven decades and has no resolution until today. It is a subject of debate between scholars whether the Kashmir conflict can be considered a frozen conflict or not. Thus, the thesis aims to answer this question. Academics have not yet concluded the definition for the concept of frozen conflicts. Hence, the thesis will provide the framework for the concept in the theoretical part by providing two different definitions and criteria. It will lead to the analyzes, where the Kashmir conflict will be viewed through the prism of the frozen conflicts criteria and answer the question of whether it can be considered a frozen conflict or not.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses